Implementation Strategy of Integrated Marketing Communication (IMC) to Improve Company Image: Case Study on PT. Anugerah Sawit Inti Harapan - Rico, Rico; Ariyani, Nafiah; Susanto, Didi (Pancasila International Journal of Applied Social Science, 2024)
The development of the palm oil industry is increasingly rapid, triggering intense competition among companies in this industry. One of the key factors in winning the competition is a good company image. Integrated Marketing Communication (IMC) emerged as a holistic strategy to build and improve a company's image. PT. Anugerah Sawit Inti Harapan, as a leading company in this sector, faces the challenge of strengthening their corporate image amidst market dynamics. This research aims to analyze the strategy for implementing Integrated Marketing Communication (IMC) in improving the company's image, with a focus on the case study of PT. Inti Harapan Palm Oil Award. This research uses a literature review method by exploring the latest literature regarding Integrated Marketing Communication and its application in the context of palm oil companies. The main research object is the IMC strategy that has been implemented by PT. Inti Harapan Palm Oil Award. Case study analysis of PT. The Inti Harapan Palm Oil Award also shows the efforts made by the company to integrate marketing communications. The conclusion of this research is that the strategy of implementing Integrated Marketing Communication can be the key to success in building and improving a company's image, especially in the palm oil industry. The practical implication of this research is the need for companies to adopt a holistic and integrated IMC approach to achieve marketing success and build a positive reputation.